ANALISIS FAKTOR KEMENANGAN GANJAR – MAHFUD PADA PEMILU TAHUN 2024 (STUDI KASUS TPS 2 DAN TPS 6 DESA WADAS, KECAMATAN BENER, KABUPATEN PURWOREJO) - Satria Nendi Herlambang (Journal of Politic and Government Studies, 2026)
This study aims to analyze the factors that influenced the victory of the candidate pair Ganjar Pranowo–Mahfud MD at TPS 2 and TPS 6 of Wadas Village, Bener District, Purworejo Regency, in the 2024 Presidential Election. Wadas Village is known as the center of the Bener Dam Conflict that directly involved Ganjar Pranowo in his role as Governor of Central Java, making Ganjar's victory in two of the village's six polling stations an electoral anomaly worth examining. This research employs a descriptive qualitative method with data collection through in-depth interviews with 14 informants who were voters at TPS 2 and TPS 6. Data analysis was conducted using three theoretical frameworks integratedly: the Voter Behavior Theory (Budiarjo, 2001; Nursal, 2004) as the main framework, the Voter Perception Theory (Sumanto, 2014; Kasali, 2017) as an intervening mechanism, and the Theory of Local Factors in Voter Behavior (Nugraha, 2021; Wahid, 2022) as a contextual moderator. The results show that Ganjar–Mahfud's victory at both polling stations was the result of simultaneously interacting factors. First, none of the informants were directly affected by the andesite mining project, thus the Wadas Conflict did not become a determining variable for rejection of Ganjar. Second, rational considerations regarding Ganjar's leadership track record as a two-term Governor of Central Java served as the primary basis for voter trust. Third, a positive perception of Ganjar's image as a populist and responsive leader—formed through social media consumption—reinforced psychological bonds, especially among young voters. Fourth, voters at both polling stations demonstrated high independence from sociological pressures, without significant influence from religious leaders, community figures, or family. These findings indicate that voter behavior cannot be reduced to a single variable, but is rather a product of complex negotiations among rational, psychological, local, and informational factors within a highly specific socio-political context.